Ingesting Self-Grown Produce and Seropositivity for Hepatitis E in the United States - Thomas M. Diehl; Daniel J. Adams; Cade M. Nylund (Gastroenterology Research and Practice, 2018)
Background. Hepatitis E virus (HEV) is a major cause of hepatitis in developing and industrialized countries worldwide. The modes of HEV transmission in industrialized countries, including the United States, remain largely unknown. This study is aimed at evaluating the association between HEV seropositivity and consumption of self-grown foods in the United States. Methods. Cross-sectional data was extracted from the 2009–2012 National Health and Nutrition Examination Survey (NHANES). Data from the dietary interview and the serum HEV IgG and IgM enzyme immunoassay test results were linked and examined. Univariate and multivariable logistic regression models were used to evaluate the significance and effect size of an association between self-grown food consumption and hepatitis E seropositivity. Results. The estimated HEV seroprevalence in the civilian, noninstitutionalized US population was 6.6% in 2009–2012, which corresponds to an estimated hepatitis E national seroprevalence of 17,196,457 people. Overall, 10.9% of participants who ingested self-grown foods had positive HEV antibodies versus 6.1% of participants who did not consume self-grown foods (P<0.001; odds ratio (OR) 1.87; 95% CI 1.41–2.48). In the age-stratified multivariable analysis, the correlation between ingesting self-grown foods and HEV seropositivity was significant for participants 40–59 years old, but not overall, or for those < 40 years or ≥60 years. Conclusions. Ingesting self-grown food, or simply the process of gardening/farming, may be a source of zoonotic HEV transmission.